Renewable Energy Management: Challenges in the Indian Industrial Sector - Mukherjee, Abhijeet (Digital Repository of Theses - SSBM Geneva, 2025)
This study examined the viability, challenges encountered, and sustainability of renewable energy in the industrial sector. The goal of the study was to give recommendations for industrial organizations that want to change towards the use of sustainable energy with reasonable costs. The main research questions focus on problems of implementation of RE (Renewable Energy) in industrial facilities, the regional differences of sources of RE including wind, solar, hydro sources in different regions of India and developing an overall strategic plan to integrate RE in industries. The research method used in the study is descriptive research with a quantitative strategy the research instruments used were a structured questionnaire survey of 300 respondents in 300 industrial enterprises across five regions of India. These regions were chosen concerning their specific climatic environment and energy mix such as hot and dry, hot and humid, coastal areas and hilly regions. The data was analysed with the help of IBM SPSS software where the emphasis was made on the ordinal regression to determine the effects of challenges and barriers for RE adoption. According to the analysis done with the help of such data, one can conclude that there is enough evidence to reject the null hypothesis and to state that there are very serious obstacles that prevent the integration of renewable energy in industrial contexts. The study gives specific suggestions to the industrial organizations on how to eliminate these barriers and use energy efficiently according to the climate change objectives. Thus, this research enhances the understanding of RE management in the industrial sectors, as well as provides direction towards economic and environmental sustainability.